Evaluation of a micromethod gallery (API Staph) for the identification of staphylococci and micrococci. Issue 6 (June 1982) - Marples, R R; Richardson, J F
Abstract : A collection of 300 well-characterised strains of staphylococci and micrococci was examined by a commercially available gallery micromethod (API Staph). The results were compared with biotyping by conventional methods. The gallery micromethod broadly agreed with the biotyping scheme used but gave an identification from the index supplied in less than 30% of the trials. Reproducibility was better after 48 h incubation than after 24 h but was poor for the tests for phosphatase and acetoin. When compared with the results of conventional tests, the tests for acetoin, phosphatase and urea were unsatisfactory.